Study the Distribution of Rotavirus Genotypes in Vaccinated and non Vaccinated Children in Babylon Province - Mahdi Mutlak, Qassim; Abdulridha, Manal Khalid; M Abbas Al-Huseini, Laith (Iraqi Journal of Pharmaceutical Sciences, 2021)
Rotaviruses, a major cause of gastroenteritis in children worldwide accounts for around half a million deaths annually. Vaccine against the virus has been recommended by the WHO to be involved in the national immunization program.To evaluate the genetic characterization of rotavirus among children with acute gastroenteritis in Babylon province is warranted. Children complained of diarrhea with rotavirus infection detected in their stool were involved in the study. The age range was 10 months to 60 months and with retrogradechecking of rotavirus vaccine history. Rotavirus genotypes were detected by reverse transcription-polymerase chain reaction (RT-PCR).A total number of 40 children with rotavirus gastroenteritis were used to examine the rotavirus genotyping distribution. The prevalent genotypes were found to be G1, G9, and G2. No significant difference in the distribution of the length of diarrhea according to genotype. Vaccinated children exhibited significantly higher percentage of G2 while G1 and G9 were presented more considerably in not vaccinated children.We detected a variety of rotavirus strains includingthe major global genotypes.Obviously, rotavirus strains are continuing to vary in Iraq. The vaccination changes the genotype prevalence and this situation may create challenges to the effectiveness of rotavirus vaccines and planning for future polices. Keywords: Rotavirus, Vaccine, Genotype.